Mathieu Forceps: A Learners Aid for Positioning the Weldable Molar Tube. Issue 1 (January 2021) - Ram, RSVM Raghu; Ranganayakulu, I; K, Anand Viswanadh
Lack of control while handling tiny objects like weldable molar tubes is the most common problem faced by the learners in orthodontics. They are prone to slippage and at times alter in position during spot welding. Here, we provide an easy-going clinical tip for accurate positioning and grasping of weldable molar tubes through spot welding using the Mathieu forceps.